Inducing Oxalobacter formigenes Colonization Reduces Urinary Oxalate in Healthy Adults - Sonia Fargue; Mangesh Suryavanshi; Kyle D. Wood; Joseph J. Crivelli; Robert A. Oster; Dean G. Assimos; Aaron Miller; John Knight (Kidney International Reports)
Introduction: Oxalate-degrading intestinal bacteria, including the oxalate-degrading specialist, Oxalobacter formigenes (O formigenes), have the potential to reduce urinary oxalate excretion in humans, and thus limit the risk of calcium oxalate kidney stone formation. The aim of this proof-of-concept study, which was performed in healthy adults, was to demonstrate that ingestion of live O formigenes is safe, can establish sustainable gut colonization, and reduce urinary oxalate excretion. Methods: Twenty-two healthy adults without a history of kidney stones and not colonized with O formigenes ingested diets controlled in oxalate and calcium. In these participants, 24-hour urine and stool oxalate levels were quantified using ion chromatography coupled with mass spectrometry before and after ingestion of O formigenes. Results: All 22 participants were successfully colonized after a single dose of O formigenes (∼1010 cells); 10 remained colonized for at least 1 year. Colonization was lost in 11 participants, of whom 9 reported antibiotic use. Six participants who lost colonization were redosed, and 5 were successfully recolonized. Stool oxalate concentration and urine oxalate excretion significantly decreased by 54% and 14%, respectively, with varied responses after colonization. Microbiome molecular analyses of precolonized stool samples highlighted the abundance and diversity of other potential oxalate-degrading bacteria, which may have influenced the effect of O formigenes colonization on urinary oxalate excretion. Conclusion: These findings support future investigations to examine the effectiveness of O formigenes colonization in reducing urinary oxalate excretion in disease cohorts, including calcium oxalate kidney stone formers with enteric hyperoxaluria.